UJI EFEKTIVITAS SALEP EKSTRAK DAUN KIRINYUH (Chromolaena odorata) TERHADAP PENYEMBUHAN LUKA SAYAT PADA MENCIT (Mus musculus) - Fadila Harifa, Nur; Hartati; Palennari, Muhiddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The skin is the main protection of the body that is susceptible to wounds, so it requires effective treatment both medically and traditionally to restore its normal function. One potential plant is kirinyuh (Chromolaena odorata) which contains phenol compounds, flavonoids, saponins, steroids, and essential oils as anti inflammatory. This study aims to evaluate the effectiveness of giving kirinyuh leaf extract ointment with concentrations of 15%, 20%, and 25% on the healing process of incision wounds in mice (Mus musculus). The research methods used are laboratory experiments which include the stage of making extracts, phytochemical screening, making concentration variations, testing antibacterial activity, making ointment preparations with hydrocarbon base, physical testing of ointments, and effectiveness tests on test animals. The results of the study showed that the administration of kirinyuh leaf extract ointment had a significant influence on the healing of cut wounds in mice. The 20% concentration was found to be the most effective dose in pharmacological studies, while the 25% concentration was the most effective dose in achieving the highest perfect wound closure on day 9.